2002
DOI: 10.1191/1365782802lt047oa
|View full text |Cite
|
Sign up to set email alerts
|

A field study of occupant controlled lighting in offices

Abstract: A study of 14 open-plan offices equipped with occupant controlled general lighting recorded achieved workstation lighting conditions at a number of times of the year. The results confirmed the occurrence of a wide range of workstation lighting levels, many significantly below CIBSE Code recommendations, with average electrical loadings due to lighting in the order of 55% of maximum. System con-figuration had a significant influence on luminaire output, illuminances and energy consumption. In general the lowest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 15 publications
2
36
0
Order By: Relevance
“…Specifically, 27 percent of participants in the Dimming Control condition choose to work above 500 lx, but only 7 percent choose to work below 300 lx. This divergence at low illuminances may be a matter of the greater contribution of daylight in one study 6 and the higher minimum illuminance in the other. …”
Section: How Do the Chosen Illuminances Relate To Recommendations?mentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, 27 percent of participants in the Dimming Control condition choose to work above 500 lx, but only 7 percent choose to work below 300 lx. This divergence at low illuminances may be a matter of the greater contribution of daylight in one study 6 and the higher minimum illuminance in the other. …”
Section: How Do the Chosen Illuminances Relate To Recommendations?mentioning
confidence: 99%
“…Similar results have been found in field studies where stepped or continuous dimming is available. Moore et al 6 reported that in their study of fourteen offices in the UK, 60 percent of occupants had chosen to work at an illuminance below 300 lx in winter and 43 percent chose to do so in summer. Only 17 percent chose an illuminance above 500 lx in winter and 30 percent did so in summer.…”
Section: How Do the Chosen Illuminances Relate To Recommendations?mentioning
confidence: 99%
See 2 more Smart Citations
“…The above study was followed by a third investigation two years later, from January to March, which included a questionnaire administered to the occupants to investigate luminous conditions and user attitudes toward the lighting control systems [56][57][58]. Seven of the 14 UK office buildings visited incorporated user-controlled lighting (191 respondents), whereas seven had no user control (161 respondents).…”
Section: Lighting Control Systemsmentioning
confidence: 99%